Salt-Losing Tubulopathies in Children: What’s New, What’s Controversial? - Robert Kleta; Detlef Böckenhauer (2017)
Renal tubulopathies provide insights into the inner workings of the kidney, yet also pose therapeutic challenges. Because of the central nature of sodium in tubular transport physiology, disorders of sodium handling may affect virtually all aspects of the homeostatic functions of the kidney. Yet, owing to the rarity of these disorders, little clinical evidence regarding treatment exists. Consequently, treatment can vary widely between individual physicians and centers and is based mainly on understanding of renal physiology, reported clinical observations, and individual experiences. Salt-losing tubulopathies can affect all tubular segments, from the proximal tubule to the collecting duct. But the more frequently observed disorders are Bartter and Gitelman syndrome, which affect salt transport in the thick ascending limb of Henle's loop and/or the distal convoluted tubule, and these disorders generate the greatest controversies regarding management. Here, we review clinical and molecular aspects of salt-losing tubulopathies and discuss novel insights provided mainly by genetic investigations and retrospective clinical reviews. Additionally, we discuss controversial topics in the management of these disorders to highlight areas of importance for future clinical trials. International collaboration will be required to perform clinical studies to inform the treatment of these rare disorders.